Media Power and Politics: Analysis of the Episode the Waldo Moment of Black Mirror from the Theories of Lazarsfeld - Londoño Proaño, Cristián (My University, 2025)
This study analyzes the episode The Waldo Moment of Black Mirror using Paul Lazarsfeld and Robert K. Merton’s theories on the role of the media. The objective is to understand how the media confer status on media figures and transform them into political leaders, through the conditions of monopolization, channeling and complementation. The analysis is based on a theoretical approach that relates the ideas of Lazarsfeld and Merton to the narrative of the episode. It examines how the lack of counterpropaganda, the reinforcement of existing attitudes and direct contact with the public allow Waldo, a fictional character, to gain political relevance. The results show that the media can legitimize entertainment figures as political actors, using media exposure to channel social discontent. Waldo’s case reveals the power of the media to activate predispositions in voters and turn media personalities into political symbols.
Keywords: Communication; Politics; Public Opinion; Science Fiction